Ответы 1

  •  \frac{6}{x-2} + \frac{5}{x} =3 \\  \\ 6x+5(x-2)=3x(x-2) \\ 6x+5x-10=3 x^{2} -6x \\ 3 x^{2} -6x-6x-5x+10=0 \\ 
3 x^{2} -17x+10=0 \\ D= (-17)^{2} -4*3*10=169 \\  \sqrt{D} =13 \\  \\ x1= \frac{17-13}{6} = \frac{4}{6} = \frac{2}{3}  \\  \\ x2= \frac{17+13}{6} =5
    • Автор:

      simmons
    • 5 лет назад
    • 0
  • Добавить свой ответ

Еще вопросы

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years